Marketing Strategy of Small and Medium Enterprises (MSMES) Through Instagram in the Marketing Era 4.0 - Ni Komang Mela Tri Utari (Universitas Warmadewa, 2021)
The purpose of this research is to understand and describe how the marketing strategy of MSMEs via Instagram in the Marketing 4.0 era. The data collection technique used was in-depth interviews with the owner of Zeen Shake and its customers as many as 70 people. The selection of informants was carried out by a purposive sampling method and the data collected were analyzed using the Nvivo software version 12. The results of this study showed that Zeen Shake carried out a marketing strategy on Instagram by uploading photos and providing information in captions, providing promos on certain days, and also upload testimonials from consumers. Besides, researchers got new findings, namely Zeen Shake also markets its products through the mouth to mouth marketing or Word of Mouth Marketing (WOMM). In the current era of Marketing 4.0, a new customer path was found (New Customer Path), from 4A (Aware, Attitude, Ask, Act Again) to 5A (Aware, Appeal, Ask, Act, Advocate). This happens because of the use of technology which causes all people to connect with one another.